Voices of Change: 20 Indian Artists (Mumbai; Marg Publications, 2010)
Artists: Baiju Parthan, Jayashree Chakraborty, Surendran Nair, Pushpamala N., N. N. Rimzon, Anita Dube, Nataraj Shetty, Sudarshan Shetty, Atul Dodiya, Bose Krishnamachari, Anju Dodiya, Subodh Gupta, Shibu Natesan, T. V. Santhosh, N. S. Harsha, Bharti Kher, Jagannath Panda, Riyas Komu, Jitish Kallat, Shilpa Gupta. Contributors: Gayatri Sinha, Latika Gupta, Adip Dutta, Ranjit Hoskote, Parul Dave Mukherji, R. Nandakumar, Deepali Dewan, Grant Watson, Vyjayanthi V. Rao, Arshiya Lokhandwala, Nancy Adjania, Deeksha Nath, Shaheen Merali, Sharmini Pereira, Brinda Kumar, Ullekh N. P., Sasha Altaf. Baiju Parthan; Jayashree Chakraborty; Surendran Nair; Pushpamala N.; N N Rimzon; Anita Dube; Nataraj Sharma; Atul Dodiya; Sudarshan Shetty; Bose Krishnamachari; Anju Dodiya; Subodh Gupta; Shibu Natesan; T V Santhosh; N S Harsha; Bharti Kher; Jagannath Panda; Riyas Komu; Jitish Kallat; Shilpa Gupta
English
Keywords: N5300-7418 Visual Arts- History; India